Real‐world experience with belantamab mafodotin therapy for relapsed/refractory multiple myeloma: A multicentre retrospective study. (7th October 2022) - Shragai, Tamir; Magen, Hila; Lavi, Noa; Gatt, Moshe; Trestman, Svetlana; Zektser, Miri; Ganzel, Chezi; Jarchowsky, Osnat; Berger, Tamar; Tadmor, Tamar; Leiba, Merav; Hertzog‐Tzarfaty, Katrin; et al.
Summary: Belantamab mafodotin, an immuno‐conjugate targeting B‐cell maturation antigen, showed single‐agent activity in phase 1 and 2 studies, and was recently approved for heavily pretreated relapsed/refractory multiple myeloma (RRMM) patients. Real‐world data and long‐term follow‐up are scarce. We conducted a multisite retrospective study aimed to assess safety and efficacy of belantamab mafodotin monotherapy administered via the GSK expanded access compassionate care programme. One‐hundred and six RRMM patients were treated with belantamab mafodotin between July 2019 and March 2021. The median age was 69.4 years. Patients were heavily pretreated with a median of six (range 2–11) prior therapy lines. Major adverse effects included ocular toxicity (keratopathy 68.4%, grade ≥3: 40.5%; blurred vision 36.8%, grade ≥3: 6.3%), thrombocytopenia (27.4%, grade ≥3: 17.9%) and infections (11.3%, grade ≥3: 7.5%). Median follow‐up time was 11.9 [95% confidence interval (CI) 10.0–13.8] months. Overall response rate was 45.5%. Median progression‐free survival was 4.7 (95% CI 3.5–5.9) months in the entire cohort and 8.8 (95% CI 6.6–10.9) months among responders. Median overall survival was 14.5 (95% CI 9.5–19.6) months, and not reached for responders. To conclude, in a real‐world setting, belantamab mafodotin monotherapy showed efficacy comparable with the prospective clinical trials, with a tolerable toxicity profile.